PREVALENCE OF MULTI DRUG RESISTANT GRAM-NEGATIVE BACTERIA AND ITS SUSCEPTIBILITY PATTERNISOLATED FROM ADMITTED PATIENTSIN A HOSPITAL OF CENTRAL INDIA;AN EMERGING GLOBAL PROBLEM - Saraswat, Dr.Ashish; Gawali, Deepak; Mishra, Abhi; Sharma, Dr Nidhi; Rastogi, Ashok Kumar; Ansari, Mehrunisha (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction:The multi-drug resistant gram-negative bacterial infections are the principle threats tothe critically ill patients.Multidrug-resistant Gram-negative rods (MDR-GNR) are emerging as amajor challenge to human health.The prevalence of drug-resistant cases is increasing globally.However, the impact of these infections on the patient’s clinical outcome has not yet been clearlyevaluated.Aim:Todetermine the incidence and associated clinical outcome of multi-drug resistant gram-negative bacterial infections.Materials and Methods:This record-based retrospective cross-sectional study was designed toanalyseMDR-GNB positive cases at a tertiary care hospital of central India. MLBMedical collegewith attached.Hospital is a700-bedreferral tertiary care centre.An increase of MDR-GNB was seenfrom September 2022 to June 2023 in the hospital. A retrospective analysis of blood culture GNB-positive samples was performed to evaluate MDR-GNB-positive cases at admission.Results:The total number of positive blood cultures inSeptember2022toJune2023, November toJanuary 2023and February to April2023 were 236,186and206, respectively, with 76.83%,80.%and71.83% GNB-positive. Total MDR-GNB-positive cases were27.08%,34.98% and32.65%,respectively, and amongst these MDR-GNB, 24%, 32% and5% where positive at time of admissiontothe hospital. The MDR-GNB wereEscherichiacoli,Klebsiella,Acinetobacter,PseudomonasandEnterobacter,Klebsiellapneumoniae,Acinetobacterspp.,Pseudomonas aeruginosaandEscherichiacolihave alarming degrees of antimicrobial resistance and are associated with high mortality andmorbidity.Conclusion:The incidence of multi-drug resistant gram-negative bacterial infections was remarkablyhigh in our hospitals and showed a significant association with healthcare-associated infections andin-hospital-mortality.